Obtenção de microcápsulas do extrato de erva cidreira (Melissa officinalis L.), pelo processo de gelificação iônica: caracterização dos compostos bioativos e da capacidade antioxidante - Oliveira, Jéssica Moura de (2020)
In the diversity of Brazilian flora, the plant species lemongrass, Melissa officinalis L., is one of the most important species in the Lamiaceae family. The use of plant extracts has been emerging in scope by the scientific community, due to its chemical composition enriched by the presence of bioactive compounds of natural origin. The great interest in bioactive compounds, stimulates the development of innovative research and technologies, which identify the properties and applications of these substances, which, when consumed orally, have their bioactive ingredients subjected to rapid gastrointestinal metabolism, undergoing transformation in their chemical structure and changes in its bioactivity. In order to guarantee its health benefits, it is essential to ensure stability in the gastrointestinal tract and allow a controlled release. The protection of bioactive ingredients in the form of coating and encapsulation is necessary to increase stability and offer controlled release, in addition to improving the bioavailability of these compounds. As well as, detailed studies are needed to characterize the constituents in plant extracts. The objective was to obtain microcapsules of the lemon balm extract, Melissa officinalis L., by the process of ionic gelation, evaluating the physical-chemical changes and the effects on the preservation of bioactive compounds. The present study evaluated the chemical composition of one of the most consumed herbs among the population, Melissa officinalis L, lemon balm, performing physical chemical, carotenoid and chlorophyll analyzes, analysis of total phenolic compounds, total flavonoids, antioxidants, FTIR and volatile compounds, thus defining the extract obtained from the fresh plant sample in infusion at 80 ° C, as the best form of extraction of bioactive compounds for submission to the microencapsulation process. An infusion of lemon balm containing the microcapsules was prepared as the final product and after the analyzes carried out, satisfactory values were obtained for the response variables of the total phenolic compounds, total flavonoids, antioxidants and volatile compounds, indicating the use of the lemon balm in its form. in natura through infusion at 80 ° C for better use of bioactive compounds.